The monomeric C-reactive protein level is associated with the increase in carotid plaque number in patients with subclinical carotid atherosclerosis - Melnikov, Ivan; Kozlov, Sergey; Pogorelova, Olga; Tripoten, Maria; Khamchieva, Leyla; Saburova, Olga; Avtaeva, Yuliya; Zvereva, Maria; Matroze, Evgeny; Kuznetsova, Tatiana; Prokofieva, Lyudmila; Balakhonova, Tatiana; et al. (Frontiers in Cardiovascular Medicine, 2022)
The high-sensitivity C-reactive protein (hsCRP) assay measures the level of the pentameric form of CRP in blood. Currently, there are no available assays measuring the level of the monomeric form of CRP (mCRP), produced at sites of local inflammation. We developed an assay measuring the mCRP level in blood plasma with functional beads for flow cytometry. The assay was used to measure the mCRP level in 80 middle-aged individuals with initially moderate cardiovascular SCORE risk. By the time of the mCRP measurement, the patients have been followed up for subclinical carotid atherosclerosis progression for 7 years. Ultrasound markers of subclinical atherosclerosis, which included plaque number (PN) and total plaque height (PH), were measured at baseline and at the 7th-year follow-up survey. Inflammatory biomarkers, including mCRP, hsCRP, inteleukin-6 (IL-6) and von Willebrand factor (VWF) level, were measured at the 7th-year follow-up survey. The median level of mCRP was 5.2 (3.3; 7.1) µg/L, hsCRP 1.05 (0.7; 2.1) mg/L, IL-6 0.0 (0.0; 2.8) pg/mL, VWF 106 (77; 151) IU/dL. In the patients with the mCRP level below median vs. the patients with the median mCRP level or higher, change from baseline in PN was 0.0 (0.0; 1.0) vs. 1.0 (1.0; 2.0) and PH 0.22 (-0.24; 1.91) mm vs. 1.97 (1.14; 3.14) mm, respectively (p <0.05). The adjusted odds ratio for the formation of new carotid atherosclerotic plaques was 4.7 (95% CI 1.7; 13.2) for the patients with the median mCRP level or higher. The higher mCRP level is associated with the more pronounced increase in PN and PH in patients with normal level of traditional inflammatory biomarkers and initially moderate cardiovascular SCORE risk.